PENGARUH CRM DAN CUSTOMER EXPERIENCE TERHADAP KEPUTUSAN PEMBEIAN ULANG MELALUI BRAND TRUST PADA PT. NASMOCO PEMUDA - Rahmadewi, Triyani; Farida, Naili; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
The research was motivated by the decrease in the number of consumers who served at PT. Nasmoco Pemuda. The aim of this research is conducted to determine the influence of customer relationship management and customer experience support to re-purchasing through brand trust. The population is all consumers who served in 2014 . While the sample of 100 consumers, with sample technique used was purposive sampling. The analysis used in this research is the Path Analysis using software SPS 19.0, which previously tested the validity, reliability, correlation coefficient, simple and multiple regression analysis, the coefficient of determination, and signification test (t test and F test) first. The result of this research approved that customer relationship management (X1) and customer experience (X2) partially or simultaneously can influenced brand trust (Z) and re-purchasing (Y). According the result of path analysis showed that brand trust variable is intervening variable towards re-purchasing in this research.